DISEÑO DE UNA CÁMARA DE ENFRIAMIENTO PARA EL ALMACENAMIENTO Y CATEGORIZACIÓN DE LA COLIFLOR, BRÓCOLI Y ZANAHORIA EN EL CANTÓN QUEVEDO - Espinoza Romero, Jhon Eliecer (2023)
The present research work proposes the design of a cooling chamber for the storage and categorization of broccoli, cauliflower and carrot in the Quevedo canton. An investigation was carried out on the problems of the waste of vegetable products that are in the Quevedo market, this waste occurs since the vegetables that arrive from the central mountains to the market still retain that cold point that is inside the market. the vegetables, as the days go by, the dew point of the product begins to decompose, so that is where you see the wilting and black spots due to the decomposition of the product, then when it reaches the consumer it has a bitter taste and is impossible to ingest.